Rhizoctonia solani kuhn, a soil-borne and seed-borne pathogen of mungbean in Malaysia. - Nik, Wan Zainun; Janggu, Ngenang (1980)
A study on some aspects for the pathogenicity and control of three isolates of Rhizoctonia solani has been investigated. Rhizoctonia isolates were taken from infected root, leaf and the seed of mungbean cv. U Th. All the isolates were highly pathogenic and virulent to mungbean resulting in severe pre- and post-emergence damping off and severe pod rot. An invitro study to test the efficiency of fungicides showed that Brassicol gave the best inhibition of growth of rhizoctonia compared to Thiram, Captan, Ls-74-783 and Busan.